AXIOMATIC DESIGN AS SUPPORT FOR DECISION-MAKING IN A DESIGN FOR MAINTENANCE IMPROVEMENT MODEL: A CASE STUDY - Pedrozo, Jorge (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
Decision-making is one of the most critical issues in design models. The design of new Maintenance methodologies that improve the levels of reliability, maintainability and availability of equipment has roused a great interest in the last years. Axiomatic Design (AD) is a design theory that provides a framework to decision-making in the designing process. The objective of this paper is to present the validation of a new maintenance improvement model as an alternative model to improve maintenance process.